Publisher Correction: Selective enhancement of optical nonlinearity in two-dimensional organic-inorganic lead iodide perovskites - F. O. Saouma; C. C. Stoumpos; J. Wong; M. G. Kanatzidis; J. I. Jang (Nature Communications, 2017)
In the PDF version of this article, Eq. 5 is missing all elements after the equals sign. The correct version of Eq. 5 is given below. The HTML version of the paper was correct from the time of publication. $$\begin{array}{ccccc}\\ G_2\left( x \right) = & \frac{1}{{(2x)^6}}\left\{ \begin{array}{l}4[1 - (1 - x)^{3/2} - (1 + x)^{3/2}] - \frac{3}{4}x^2[(1 - x)^{ - 1/2} + (1 + x)^{ - 1/2}]\\ + 6x\{ (1 - x)^{1/2} - (1 + x)^{1/2}\} + 2[H(1 - 2x)(1 - 2x)^{3/2} + (1 + 2x)^{3/2}]\end{array} \right\}\\ \\ & + \frac{1}{{(2^{10}x^5)}}\left\{ {70x^2 + 3x[(1 - x)^{ - 1/2} - (1 + x)^{ - 1/2}] - \frac{1}{2}x^2[(1 - x)^{ - 3/2} + (1 + x)^{ - 3/2}]} \right\}\\ \end{array}$$ G 2 x = 1 ( 2 x ) 6 4 [ 1 - ( 1 - x ) 3 ∕ 2 - ( 1 + x ) 3 ∕ 2 ] - 3 4 x 2 [ ( 1 - x ) - 1 ∕ 2 + ( 1 + x ) - 1 ∕ 2 ] + 6 x { ( 1 - x ) 1 ∕ 2 - ( 1 + x ) 1 ∕ 2 } + 2 [ H ( 1 - 2 x ) ( 1 - 2 x ) 3 ∕ 2 + ( 1 + 2 x ) 3 ∕ 2 ] + 1 ( 2 10 x 5 ) 70 x 2 + 3 x [ ( 1 - x ) - 1 ∕ 2 - ( 1 + x ) - 1 ∕ 2 ] - 1 2 x 2 [ ( 1 - x ) - 3 ∕ 2 + ( 1 + x ) - 3 ∕ 2 ]